Mathematical methods for physics and engineering - Blennow, Mattias (New york CRC Press, 2018)
"This new textbook, suitable for advanced undergraduate and graduate students in physics and engineering, covers mathematical methods with an accessible and clear writing style. Mattias Blennow employs detailed worked examples (around 40 per chapter) to teach the topics in a truly "hands-on" manner, and includes in-depth discussions of a wide range of subjects. The book is unique in drawing upon applications from physics, rather than mathematical examples, to ensure students are fully equipped with the tools they need. The book is also distinctive in the coverage it devotes to modelling, and to oft-neglected topics such as Green's functions. More than 50 end-of-chapter problems are provided"--
Keywords: Mathematical physics; Engineering mathematics